Порядок увольнения в связи с сокращением численности штата работников, а также ликвидацией препдприятия - Сосна, Александр; Константинов, Олег (Tipografia "A&V" Poligraf, Comrat, 2019)
The submission examines the features of reducing the number and staff of the enterprise as an institution of the branch of labor law, the legal basis for terminating the individual labor contract on the initiative of the employer and preventing their abuse, discloses the concepts used in the process of studying this institute, discloses the prohibition of the reduction employer, as well as guarantees and compensation provided to persons dismissed by the employer He doesn’t need to reduce the number and staff of the enterprise and liquidate the enterprise or terminate the activity of the individual employer.
Keywords: employee; employer; reduction in the number of employees; staff reduction